Human-centered leadership strategies for religious and moral development in early childhood education - Afrida Yuli; Luthfatun Nisa; Jamiludin Usman; Rasyidi (CV. SPDFHarmony, 2025)
Background: Early childhood education is a critical stage for the development of religious and moral values, as children undergo rapid cognitive, emotional, and behavioral growth. School leadership plays a strategic role in shaping learning environments that support value formation. However, leadership practices in early childhood education are still rarely examined from a human factor perspective. Aims: This study aims to analyze human-centered leadership strategies implemented by school principals in fostering religious and moral development among early childhood learners and to identify human-related constraints in their implementation. Method: This study employed a qualitative descriptive approach. Data were collected through direct field observations, participatory observation, and documentation at an early childhood education institution. The data focused on leadership practices, daily learning activities, and interactions among principals, teachers, students, and parents. Data analysis followed the stages of data reduction, data organization, interpretation, and conclusion drawing. Results: The findings reveal that principals implemented three main human-centered leadership strategies: habituation, role modeling, and partnership. Habituation involved routine religious and moral activities, role modeling was demonstrated through disciplined and ethical behavior by educators, and partnership emphasized collaboration with teachers, parents, and the community. Despite positive impacts on children’s moral and religious development, several challenges were identified, including limited facilities, insufficient variation in teaching methods, and negative environmental influences such as excessive digital device use. Conclusion: Human-centered leadership strategies contribute significantly to the development of religious and moral values in early childhood education. Strengthening institutional support and collaboration with parents is essential to optimize these strategies.